Three-dimensional perfluoroalkyl chain-modified covalent organic framework, preparation method and application thereof

By synthesizing a covalent organic framework modified by three-dimensional perfluoroalkyl chains and adding phosphoric acid, a proton exchange membrane material with high temperature stability and excellent proton conduction performance is formed, which solves the problem of unstable proton exchange membranes in the prior art at high temperatures and achieves a significant improvement in proton conductivity.

CN115926080BActive Publication Date: 2025-05-09NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211590809.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-05-09
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing proton exchange membrane is unstable under high temperature conditions, and is difficult to synthesis and control conditions, resulting in limited application in fuel cells.

Method used

A covalent organic framework modified by three-dimensional perfluoroalkyl chains was synthesized by using 2,5-bis(perfluoroalkyl)-terbyl-p-diformaldehyde and tetrade (4-aminophenyl)methane as raw materials, and phosphoric acid was added on it to form a H3PO4@3D-COF-Fn-X proton exchange membrane material.

Benefits of technology

The stability and proton conduction performance of the proton exchange membrane at high temperatures are improved. The proton conductivity of H3PO4@3D-COF-F6-35% can reach 6.11×10-3S cm-1, which is about 10 times higher than the proton conductivity of previous technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926080B_ABST
    Figure CN115926080B_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional perfluoroalkyl chain-modified covalent organic framework, a preparation method and its application. The covalent organic framework is a three-dimensional quadrilateral topological structure synthesized by connecting two aldehyde groups of 2,5-bis(perfluoroalkyl)-terphenyl-p-dicarboxaldehyde and four amino groups of tetra(4-aminophenyl)methane to form a C=N covalent bond, and is prepared by a solvent thermal method using tetra(4-aminophenyl)methane and 2,5-bis(perfluoroalkyl)-terphenyl-p-dicarboxaldehyde as raw materials and acetic acid as a catalyst. The covalent organic framework modified by the three-dimensional perfluoroalkyl chain of the present invention has good crystallinity and thermal stability, and the proton exchange membrane material formed by compounding it with phosphoric acid shows good proton conductivity at high temperature, and is suitable for the field of fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of covalent organic framework compounds and relates to a three-dimensional perfluoroalkyl chain-modified covalent organic framework, a preparation method and application thereof in proton conduction. Background Art

[0002] The proton exchange membrane is the core part of the proton exchange membrane fuel cell, and its performance directly affects the performance of the entire battery. The existing proton exchange membranes, such as the commercial Nafion membrane, have good proton conductivity (0.1Scm -1 ), but it is not applicable under high temperature conditions. Therefore, the development of anhydrous proton conductors that can be used at high temperatures is of great significance for the development and application of fuel cells.

[0003] At present, introducing non-volatile liquid acids into porous materials is a promising strategy for constructing anhydrous proton conductors. However, most porous materials have weak coordination or covalent bonds, which makes them unsuitable in acidic environments due to structural instability and performance destruction. The key to constructing such anhydrous porous material proton conductors lies in the stability of the material itself. However, most of the porous material proton conductors with stable structure and excellent performance under high temperature conditions have problems such as difficult synthesis, difficult control of synthesis process conditions, and difficulty in large-scale synthesis.

[0004] Covalent organic frameworks (COFs) are a class of organic porous crystalline materials composed of organic structural units connected by covalent bonds. The covalent organic framework is composed of different covalently connected spacers. However, unlike MOFs, these materials are mainly used for gas storage, catalysis and photoconductivity. Recently, the emergence of chemically stable COFs has paved the way for electrochemical applications, such as charge storage and proton conductivity. Moreover, the materials have the characteristics of high porosity, large specific surface area, light weight, pre-designable structure and high stability, and are considered to be promising proton conductors. By designing COFs materials with reasonable structures and combining the framework characteristics of COFs with non-volatile proton acids, proton exchange membrane materials with stable structural, thermodynamic and electrochemical properties can be obtained. Chinese patent ZL2021109317093 discloses a perfluoroalkyl chain-modified covalent organic framework, which is a quadrilateral topological structure synthesized by connecting two aldehyde groups of 2,5-bis(perfluoroalkyl)-terphenyl-p-diformaldehyde (Fn-CHO) and four amino groups of N,N,N',N'-tetra(p-aminophenyl)-p-phenylenediamine to form a -C=N- covalent bond. It is a two-dimensional structural material, among which the best-performing H3PO4@2D-COF-F8-30% has a proton conductivity of 7.5×10 -4 S cm -1 , the proton conductivity is still relatively low. Summary of the invention

[0005] One of the purposes of the present invention is to provide a three-dimensional perfluoroalkyl chain-modified covalent organic framework. The three-dimensional perfluoroalkyl chain-modified covalent organic framework is a three-dimensional quadrilateral topological structure synthesized by connecting two aldehyde groups of 2,5-bis(perfluoroalkyl)-terphenyl-p-dicarboxaldehyde (Fn-CHO) and four amino groups of tetrakis(4-aminophenyl)methane to form a -C=N- covalent bond, and its structural formula is as follows:

[0006]

[0007] The structural formula of tetrakis(4-aminophenyl)methane of the present invention is as follows:

[0008]

[0009] The structural formula of 2,5-bis(perfluoroalkyl)-terphenyl-paraformaldehyde (Fn-CHO) of the present invention is as follows:

[0010]

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned three-dimensional perfluoroalkyl chain-modified covalent organic framework, comprising the following steps:

[0012] Tetrakis(4-aminophenyl)methane and 2,5-bis(perfluoroalkyl)-terphenyl-p-diformaldehyde in a molar ratio of 1:2 are added to pure dioxane or a solvent composed of ethanol and dioxane in a volume ratio of 2:3 to 3:2, ultrasonically dispersed, added with acetic acid solution, sequentially subjected to liquid nitrogen freezing, vacuumization, and degassing treatments, sealed with a flame gun, and reacted at 120±10°C for more than 5 days to obtain a crude product, which is sequentially washed with dichloromethane, ethanol, tetrahydrofuran, and acetone, then filtered, extracted with tetrahydrofuran Soxhlet, and vacuum dried to obtain 2,5-bis(perfluoroalkyl)-terphenyl-p-diformaldehyde (3D-COF-Fn).

[0013] Preferably, the liquid nitrogen freezing, vacuuming and degassing treatments are performed at least three times.

[0014] Preferably, the concentration of the acetic acid solution is 3 to 9 mol / L, more preferably 6 mol / L.

[0015] Preferably, the Soxhlet extraction time is 12 to 48 hours.

[0016] Preferably, the vacuum drying temperature is 65° C. and the time is 12 h.

[0017] The third object of the present invention is to provide a proton exchange membrane material based on the above-mentioned three-dimensional perfluoroalkyl chain-modified covalent organic framework, which is prepared by the following steps:

[0018] The perfluoroalkyl chain-modified covalent organic framework and phosphoric acid are mixed in proportion, ground until the mixture is uniform, vacuum dried at 85±5°C for more than 12 hours, heated at 100°C for 5-6 hours under an argon protective atmosphere, and pressed into sheets after cooling to prepare a proton exchange membrane material (H3PO4@3D-COF-Fn-X, X is the percentage of phosphoric acid in the total mass of the membrane).

[0019] In a specific embodiment of the present invention, phosphoric acid accounts for 35% of the total mass of the separator.

[0020] A fourth object of the present invention is to provide the application of the above-mentioned proton exchange membrane material based on the covalent organic framework modified with three-dimensional perfluoroalkyl chains in fuel cells.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The present invention uses 2,5-bis(perfluoroalkyl)-terphenyl-p-diformaldehyde and tetrakis(4-aminophenyl)methane as raw materials to synthesize a three-dimensional perfluoroalkyl chain-modified covalent organic framework. By adding non-volatile proton acid phosphoric acid into the covalent organic framework material, its proton conductivity is further improved. The proton exchange membrane material of the present invention, as an electrolyte, exhibits a high proton conductivity and has excellent proton conductivity. In addition, due to the modification of the perfluoroalkyl chain and phosphoric acid doping, H3PO4@3D-COF-F n The material shows good stability and proton conductivity at higher temperatures. For example, the proton conductivity of H3PO4@3D-COF-F6-35% can reach 6.11*10 -3 S cm -1 . Compared with the inventor's H3PO4@2D-COF-F8-35% in the prior patent ZL2021109317093, the improvement is about 10 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 PXRD patterns of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8;

[0024] Figure 2 Infrared images of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8;

[0025] Figure 3 Nitrogen adsorption curves of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8;

[0026] Figure 4 Performance test diagram of ion conduction of H3PO4@3D-COF-F4-35% at different temperatures;

[0027] Figure 5 Performance test diagram of ion conduction of H3PO4@3D-COF-F6-35% at different temperatures;

[0028] Figure 6 Performance test diagram of ion conduction of H3PO4@3D-COF-F8-35% at different temperatures;

[0029] Figure 7 Performance test diagram of ion conduction of H3PO4@2D-COF-F4-35% at different temperatures;

[0030] Figure 8 The conductivity of H3PO4@3D-COF-Fn-35% (n=4, 6, 8) at different temperatures;

[0031] Fig. 9 SEM images of 3D-COF-Fn (n=4, 6, 8);

[0032] Fig.10 This is the SEM image of H3PO4@3D-COF-Fn-35% (n=4, 6, 8). DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0034] Tetrakis(4-aminophenyl)methane used in the following examples was purchased from a commercial source. 2,5-Bis(perfluoroalkyl)-terphenyl-p-dicarbaldehyde (Fn-CHO) was prepared according to Chinese Patent ZL2021109317093.

[0035] Example 1

[0036] The three-dimensional perfluoroalkyl chain-modified covalent organic framework (3D-COF-F4) is an organic framework structure formed by the Schiff base reaction of tetrakis(4-aminophenyl)methane and F4-CHO. Its structure is shown below:

[0037]

[0038] The specific steps are as follows:

[0039] Take 0.04mmol tetrakis(4-aminophenyl)methane, 0.08mmol 2,5-bis(perfluorobutyl)-terphenyl-p-diformaldehyde (F4-CHO), add 0.75mL ethanol and 0.5mL dioxane, disperse the raw materials by ultrasound to form a suspension, add 0.2mL of 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, vacuumize and degas three times, seal the tube with a flame gun, and then put it in a 120℃ oven to react for 5d; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F4 with a yield of 91%. The reaction formula is as follows:

[0040]

[0041] The preparation method of H3PO4@3D-COF-F4-35% has the following specific steps: based on the phosphoric acid accounting for 35% of the total mass of the diaphragm, 20 mg 3D-COF-F4 and 10.77 mg phosphoric acid are weighed and mixed respectively, and the mixture is fully ground in a mortar until it is evenly mixed, and then placed in a vacuum drying oven and dried at 85°C for 12 hours, and then heated at 100°C for 5 hours in an argon protective atmosphere, and cooled and pressed into a sheet to form a diaphragm (H3PO4@3D-COF-F4-35%), and a button battery is assembled, and its proton conduction curve at 30-120°C is measured.

[0042] Example 2

[0043] This embodiment is basically the same as embodiment 1, the only difference being that the solvent used is 0.5 mL of ethanol and 0.75 mL of dioxane, that is, a solvent composed of ethanol and dioxane in a volume ratio of 2:3, specifically:

[0044] Take 0.04mml tetrakis(4-aminophenyl)methane, 0.08mmol 2,5-bis(perfluorobutyl)-terphenyl-p-dicarbaldehyde (F4-CHO), add 0.5mL ethanol and 0.75mL dioxane, disperse the raw materials by ultrasound to form a suspension, add 0.2mL 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, evacuate, degas three times, seal the tube with a flame gun, and then put it in a 120℃ oven to react for 5d; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol, and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F4 with a yield of 80%.

[0045] Example 3

[0046] This embodiment is basically the same as embodiment 1, the only difference being that 0.75 mL of ethanol and 0.75 mL of dioxane are used as solvents, that is, a solvent composed of ethanol and dioxane in a volume ratio of 1:1, specifically:

[0047] Take 0.04mmol tetrakis(4-aminophenyl)methane, 0.08mmol2,5-bis(perfluorobutyl)-terphenyl-p-dicarbaldehyde (F4-CHO), add 0.75mL ethanol and 0.75mL dioxane, disperse the raw materials by ultrasound to form a suspension, then add 0.2mL of 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, evacuate, and degas three times, seal the tube with a flame gun, and then put it in a 120℃ oven to react for 72h; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol, and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F4 with a yield of 63%.

[0048] Example 4

[0049] This example is basically the same as Example 1, the only difference being that 1 mL of dioxane is used as the solvent, specifically:

[0050] Take 0.04mmol tetrakis(4-aminophenyl)methane, 0.08mmol2,5-bis(perfluorobutyl)-terphenyl-p-dicarbaldehyde (F4-CHO), add 1mL of dioxane, disperse the raw materials by ultrasound to form a suspension, then add 0.2mL of 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, evacuate, and degas three times, seal the tube with a flame gun, and then put it in a 120℃ oven to react for 5d; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol, and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F4 with a yield of 66%.

[0051] Example 5

[0052] Example 5 is basically the same as Example 1, except that the monomer is 2,5-bis(perfluorohexyl)-terphenyl-p-dicarboxaldehyde (F6-CHO), specifically:

[0053] Take 0.04mmol tetrakis(4-aminophenyl)methane, 0.08mmol 2,5-bis(perfluorohexyl)-terphenyl-p-dicarbaldehyde, add 0.75mL ethanol and 0.5mL dioxane, disperse the raw materials by ultrasound to form a suspension, then add 0.2mL of 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, evacuate, and degas three times with a flame gun, then put it in a 120℃ oven to react for 5d; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol, and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F6 with a yield of 88%.

[0054] Example 6

[0055] Example 6 is basically the same as Example 1, except that the monomer is 2,5-bis(perfluorooctyl)-terphenyl-p-dicarboxaldehyde (F8-CHO), specifically:

[0056] Take 0.04mmol tetrakis(4-aminophenyl)methane, 0.08mmol2,5-bis(perfluorooctyl)-terphenyl-p-dicarbaldehyde (F8-CHO), add 0.75mL ethanol and 0.5mL dioxane, disperse the raw materials by ultrasound to form a suspension, then add 0.2mL of 6mol / L acetic acid solution, freeze the suspension with liquid nitrogen, evacuate, and degas three times, seal the tube with a flame gun, and then put it in a 120℃ oven to react for 5d; take it out and cool it to obtain a crude product, wash and filter it three times with dichloromethane, ethyl acetate, methanol, and acetone in turn, extract it with tetrahydrofuran Soxhlet, put it in a vacuum drying oven and dry it at 65℃ for 12 hours to obtain a yellow solid 3D-COF-F8.

[0057] Comparative Example

[0058] Reference is made to the inventor’s prior patent ZL2021109317093 for preparing a two-dimensional perfluoroalkyl chain-modified covalent organic framework (2D-COF-F4).

[0059] The preparation method of H3PO4@2D-COF-F4-35% has the following specific steps: based on the phosphoric acid accounting for 35% of the total mass of the diaphragm, 20 mg of 2D-COF-F4 and 10.77 mg of phosphoric acid are weighed and mixed, and the mixture is fully ground in a mortar until it is evenly mixed. The mixture is placed in a vacuum drying oven and dried at 85°C for 12 hours, and then heated at 100°C for 5 hours in an argon protective atmosphere. The membrane (H3PO4@2D-COF-F4-35%) is cooled and pressed into a sheet, and a button battery is assembled, and its proton conduction curve at 30-120°C is measured.

[0060] Figure 1The XRD patterns of 3D-COF-F4 prepared in Example 1, 3D-COF-F6 prepared in Example 5, and 3D-COF-F8 prepared in Example 6 show that the crystal form of 3D-COF-F6 is the best, while the crystal forms of 3D-COF-F4 and 3D-COF-F8 are relatively slightly worse. At the same time, it can be seen that the covalent organic frameworks modified with perfluoroalkyl chains of different lengths all have peaks (n=4, 6, 8), which can confirm that the covalent organic framework modified with perfluoroalkyl chains has been successfully synthesized.

[0061] Figure 2 The infrared images of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8 are shown in Figure 1. The infrared images of 3D-COF-Fn (n=4, 6, 8) are at 1632 cm -1 The infrared absorption peak of the C=N bond can confirm the formation of the C=N bond. At the same time, it further proves that the covalent organic framework modified with perfluoroalkyl chains has been successfully synthesized.

[0062] Figure 3 The nitrogen adsorption curves of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8 are shown in Figure 1. By observing the nitrogen adsorption of the three COFs, it is found that the nitrogen adsorption of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8 decreases in turn. This is basically consistent with the fact that the longer the side chain, the smaller the pore, so the specific surface area decreases in turn.

[0063] Figure 4 The performance test diagram of ion conduction of 3D-COF-F4-35% at different temperatures shows that the proton conduction performance of 3D-COF-F4-35% reaches the highest at 120℃, with a maximum of 1.66×10 -3 S cm -1 .

[0064] Figure 5 The performance test diagram of ion conduction of 3D-COF-F6-35% at different temperatures shows that the proton conduction performance of 3D-COF-F6-35% reaches the highest at 120℃, with a maximum of 6.11×10 -3 S cm -1 .

[0065] Figure 6 The performance test diagram of ion conduction of 3D-COF-F8-35% at different temperatures shows that the proton conduction performance of 3D-COF-F8-35% reaches the highest at 120℃, with a maximum of 1.47×10 -3 S cm -1 .

[0066] Figure 7The performance test diagram of ion conduction of 2D-COF-F4-35% at different temperatures shows that the proton conduction performance of 2D-COF-F4-35% reaches the highest at 120°C, with a maximum of 5×10 -4 S cm -1 .

[0067] Figure 8 The conductivity of 3D-COF-Fn-35% (n = 4, 6, 8) at different temperatures is shown in Figure 2. The relationship between conductivity and temperature conforms to the Arrhenius formula, and the proton conductivity of 3D-COF-F6-35% reaches the highest at 120 °C, with a maximum of 6.11×10 -3 S cm -1 , COF modified with perfluoroalkyl chains under phosphoric acid doping has high proton conductivity and has great application prospects as a fuel cell diaphragm material.

[0068] Fig. 9 These are SEM images of 3D-COF-F4, 3D-COF-F6, and 3D-COF-F8. It can be seen from the images that 3D-COF-Fn (n=4, 6, 8) are all coral-like and have similar morphologies.

[0069] Fig.10 These are the SEM images of H3PO4@3D-COF-F4-35%, H3PO4@3D-COF-F6-35%, and H3PO4@3D-COF-F8-35%. As can be seen from the images, they are similar to the SEM images of 3D-COF-Fn (n=4, 6, 8), with little difference in morphology, and are also coral-like.

Claims

1. A three-dimensional perfluoroalkyl chain-modified covalent organic framework, characterized in that: It is a three-dimensional quadrilateral topological structure synthesized by connecting two aldehyde groups of 2,5-bis(perfluoroalkyl)-terphenyl-p-dicarboxaldehyde and four amino groups of tetra(4-aminophenyl)methane to form a -C=N- covalent bond, and its structural formula is as follows: , ,or .

2. The method for preparing a three-dimensional perfluoroalkyl chain-modified covalent organic framework according to claim 1, characterized in that: The following steps are involved: Tetrakis(4-aminophenyl)methane and 2,5-bis(perfluoroalkyl)-terphenyl-p-diformaldehyde in a molar ratio of 1:2 are added to pure dioxane or a solvent consisting of ethanol and dioxane in a volume ratio of 2:3 to 3:2, ultrasonically dispersed, added with acetic acid solution, sequentially subjected to liquid nitrogen freezing, vacuumization, and degassing treatment, sealed with a flame gun, and reacted at 120±10°C for more than 5 days to obtain a crude product, which is sequentially washed with dichloromethane, ethanol, tetrahydrofuran, and acetone, then filtered, extracted with tetrahydrofuran Soxhlet, and vacuum dried to obtain a three-dimensional perfluoroalkyl chain-modified covalent organic framework. The structural formula of the tetrakis(4-aminophenyl)methane is: , The structural formula of the 2,5-bis(perfluoroalkyl)-terphenyl-p-dicarbaldehyde is: 。 3. The preparation method according to claim 2, characterized in that: The liquid nitrogen freezing, vacuuming and degassing treatments should be performed at least 3 times.

4. The preparation method according to claim 2, characterized in that: The concentration of acetic acid solution is 3~9mol / L.

5. The preparation method according to claim 2, characterized in that: The concentration of the acetic acid solution is 6 mol / L.

6. The preparation method according to claim 2, characterized in that The Soxhlet extraction time ranged from 12 to 48 h.

7. The preparation method according to claim 2, characterized in that: The vacuum drying temperature was 65°C and the time was 12 h.

8. A proton exchange membrane material based on a covalent organic framework modified with a three-dimensional perfluoroalkyl chain, characterized in that: Prepared by the following steps: The perfluoroalkyl chain-modified covalent organic framework according to claim 1 and phosphoric acid are mixed so that phosphoric acid accounts for 35% of the total mass of the diaphragm, ground until the mixture is uniform, vacuum dried at 85±5° C. for more than 12 hours, then heated at 100° C. for 5-6 hours under an argon protective atmosphere, and pressed into tablets after cooling to prepare a proton exchange diaphragm material.

9. Use of the proton exchange membrane material based on the covalent organic framework modified with three-dimensional perfluoroalkyl chains according to claim 8 in a fuel cell.

Citation Information

Patent Citations

  • Three-dimensional covalent organic framework material, open tubular capillary electrochromatographic column and preparation method

    CN111604039A

  • Perfluoroalkyl chain modified covalent organic framework as well as preparation method and application thereof

    CN113637131A